2015
DOI: 10.1128/aac.04579-14
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Persistence Due to Biofilm Formation in Synovial Fluid Containing Prophylactic Cefazolin

Abstract: Antibiotic prophylaxis is standard for patients undergoing surgical procedures, yet despite the wide use of antibiotics, breakthrough infections still occur. In the setting of total joint arthroplasty, such infections can be devastating. Recent findings have shown that synovial fluid causes marked staphylococcal aggregation, which can confer antibiotic insensitivity. We therefore asked in this study whether clinical samples of synovial fluid that contain preoperative prophylactic antibiotics can successfully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 31 publications
3
73
2
Order By: Relevance
“…Even when SF was isolated from patients who had received high doses of prophylactic antibiotic, which leads to high concentrations of antibiotic in SF (28), biofilms formed on titanium disks over the course of 48 h (Fig. 1A), underscoring the notion that S. aureus PJIs are recalcitrant to antibiotic treatment due to the formation of biofilms (4,28). Notably, extensive biofilm-like aggregates formed within minutes after incubation of the bacteria in SF and were characterized by the attachment of fibrous material (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Even when SF was isolated from patients who had received high doses of prophylactic antibiotic, which leads to high concentrations of antibiotic in SF (28), biofilms formed on titanium disks over the course of 48 h (Fig. 1A), underscoring the notion that S. aureus PJIs are recalcitrant to antibiotic treatment due to the formation of biofilms (4,28). Notably, extensive biofilm-like aggregates formed within minutes after incubation of the bacteria in SF and were characterized by the attachment of fibrous material (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In the present study, we asked which factors are responsible for the excessively strong degree of aggregate and biofilm formation in SF, which is the basis for the notorious recalcitrance of such infections to antibiotic treatment (28). We identified the low activity of Agr and consequentially low production of PSMs as major factors contributing to that phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the synergy between CF-301 Ex vivo analysis of biofilms formed in HSF. Human synovial fluid (HSF) is known to support the formation of strong antibiotic-resistant biofilms composed of host factors (including fibrin) and bacterial proteins (including fibronectin-and fibrinogenbinding proteins) (50). We showed that biofilms formed by MRSA strain BAA-42 in HSF Antimicrobial Agents and Chemotherapy were susceptible to removal and killing by CF-301 between 4 and 24 h (Fig.…”
Section: Schuch Et Al Antimicrobial Agents and Chemotherapymentioning
confidence: 90%
“…Aggressive antibiotic therapies can reduce biofilms and control dispersed planktonic bacteria; however, eradication is difficult because of the high antibiotic concentrations that must be sustained (50,(52)(53)(54). To avoid the limitations of antibiotics, a promising new strategy was proposed based on the emerging understanding of bacteriophage lysins as antibiofilm agents (32,43).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, fibrin-rich S. aureus biofilms appear rapidly, which might decrease the efficacy of antibiotic prophylaxis (30) and blunt phagocytosis (9,11,31,32). Importantly, tPA coating prevents the first step of biofilm formation, the adhesion of S. aureus to the implant surface, thereby expanding the window of opportunity and allowing more efficient pathogen clearance.…”
Section: Discussionmentioning
confidence: 99%